Equivalent circuit modeling of piezoelectric energy harvesters - Yang, Yaowen (2014)
Last decade has seen growing research interest in vibration energy harvesting using piezoelectric materials. When developing piezoelectric energy harvesting systems, it is advantageous to establish certain analytical or numerical model to predict the system performance. In the last few years, researchers from mechanical engineering established distributed models for energy harvester but simplified the energy harvesting circuit in the analytical derivation. While, researchers from electrical engineering concerned the modeling of practical energy harvesting circuit but tended to simplify the structural and mechanical conditions. The challenges for accurate modeling of such electromechanical coupling systems remain when complicated mechanical conditions and practical energy harvesting circuit are considered in system design. In this article, the aforementioned problem is addressed by employing an equivalent circuit model, which bridges structural modeling and electrical simulation. First, the parameters in the equivalent circuit model are identified from theoretical analysis and finite element analysis for simple and complex structures, respectively. Subsequently, the equivalent circuit model considering multiple modes of the system is established and simulated in the SPICE software. Two validation examples are given to verify the accuracy of the proposed method, and one further example illustrates its capability of dealing with complicated structures and non-linear circuits.